Characteristics and outcome of elderly patients (>55 years) with acute lymphoblastic leukemia - Wenge, Daniela Vanessa; Wethmar, Klaus; Klar, Corinna A.; Kolve, Hedwig; Sauer, Tim; Angenendt, Linus; Evers, Georg; Call, Simon; Kerkhoff, Andrea; Khandanpour, Cyrus; Kessler, Torsten; Mesters, Rolf; et al. (Cancers, 2022)
Prognosis of elderly ALL patients remains dismal. Here, we retrospectively analyzed the course of 93 patients > 55 years with B-precursor (n = 88) or T-ALL (n = 5), who received age-adapted, pediatric-inspired chemotherapy regimens at our center between May 2003 and October 2020. The median age at diagnosis was 65.7 years, and surviving patients had a median follow-up of 3.7 years. CR after induction therapy was documented in 76.5%, while the rate of treatment-related death within 100 days was 6.4%. The OS of the entire cohort at 1 and 3 year(s) was 75.2% (95% CI: 66.4-84.0%) and 47.3% (95% CI: 36.8-57.7%), respectively, while the EFS at 1 and 3 years(s) was 59.0% (95% CI: 48.9-69.0%) and 32.9% (95% CI: 23.0-42.8%), respectively. At 3 years, the cumulative incidence (CI) of relapse was 48.3% (95% CI: 38.9-59.9%), and the CI rate of death in CR was 17.3% (95% CI: 10.9-27.5%). Older age and an ECOG > 2 represented risk factors for inferior OS, while BCR::ABL1 status, immunophenotype, and intensity of chemotherapy did not significantly affect OS. We conclude that intensive treatment is feasible in selected elderly ALL patients, but high rates of relapse and death in CR underline the need for novel therapeutic strategies.
Gesehen am 22.03.2022